Free movement of goods and new agreements in the aftermath of Brexit - Police, Cecilia (LUISS Guido Carli, 2022)
The main principles of EU internal market vs the new UK internal market: a background. The internal market of the European Union. UK membership: accession to the European economic community in 1973. The nature of the EU internal market and the free movement of goods. The UK internal market after the internal market act 2020. The EU common commercial policy and the post-Brexit scenario. Brexit: new agreements and legal framework. EU-UK post-Brexit relationship: a new framework for a new partnership. Brexit history and the question of sovereignty. Brexit history: the timeline. Brexit and the withdrawal agreement. Brexit and Northern Ireland protocol. Brexit and trade: perspectives on a new partnership. Brexit and trade: trade and cooperation agreement. Trade and cooperation agreement: EU-UK trade relations, institutional and governance structures. Preliminary remarks. Analysis of the TCA: trade in goods provisions. 0,0 agreement: zero tariffs, zero quotas and rules of origin. The TCA: technical barriers to trade (TBT). The TCA: sanitary and phytosanitary standards (SPS). The TCA: the principle of mutual recognition. Level playing field (LPF). The Northern Ireland protocol and the trade in goods regime. TCA’s main concerns and application issues. TCA dispute settlement mechanisms. Some conclusive remarks on TCA provisions.

The conclusion of contracts by electronic agents in the age of the Fourth Industrial Revolution : a South African perspective - Doughan, Albert Nana (University of Johannesburg, 2022)
Please refer to full text to view abstract.
Keywords: Commercial law; Contracts; Electronic data interchange; Industry 4.0

The role of good faith in South African contract law - Govender, Tashri (University of KwaZulu-Natal, 2022)
This research paper seeks to address the role that good faith plays in South African contract law by first discussing its origin and then chronologically tracing its position from pre-1994 to today. The judgements of both the Supreme Court of Appeal and the Constitutional Court will be unpacked, as a means to understand the development of good faith over the years. The position that good faith plays in foreign jurisdictions will also be discussed, for the sake of achieving a universal understanding of how good faith is perceived around the world. The research concludes by placing good faith in its current role and context in South Africa, and also proposing a way forward.
Keywords: Bona fides; Contract Law

A critical analysis of the institution of business rescue proceedings during liquidation proceedings - Krishundutt, Sanam (University of KwaZulu-Natal, 2022)
South Africa is currently undergoing harsh economic times, and as such, many companies are feeling the brunt of the situation. As a result, these companies begin to trade at a loss and are left without any other option but to liquidate their affairs in order to pay off creditors. However, with the development brought by the Companies Act 71 of 2008 (“the Act”), business rescue was introduced. Business rescue is an alternative to liquidation and it allows the company to undergo rehabilitation and continue trading if certain requirements are met. Chapter 6 of the Act aims to assist businesses in providing some sort of relief in the form of business rescue to provide them with the breathing space that they require to try and become a viable business again. Just like any new formulated concept, it is susceptible to abuse. Many companies that are already under liquidation are suspending their liquidation in favour of business rescue, despite, in some instances, the liquidation order having already been granted against the company. The Covid-19 pandemic has made the question of whether a business can suspend liquidation proceedings in favour of business rescue more prevalent as the pandemic has caused a detrimental financial impact on a number of businesses. Now more than ever businesses find themselves struggling to keep afloat, and as a result many of them have to consider the avenues of liquidation or business rescue. This dissertation aims to look at both liquidation and business rescue proceedings and decipher whether the courts were correct in their decision regarding when business rescue proceedings can be instituted during liquidation proceedings. The importance of taking into account the above is due to the fact that many companies in present day are experiencing financial difficulties, and liquidation or business rescue proceedings are the options that they are left with. However, one has to carefully consider both options, taking into account the company’s financial circumstances. This is of importance, as one needs to establish if there is a reasonable prospect of rescuing the company or not. If there were, then business rescue would indeed be the route to be taken, but if not, then liquidation proceedings would be. However, many companies that have no prospect of being rescued, and that have already opted for liquidation may want to institute business rescue proceedings to delay the inevitable and frustrate creditors, thus leading to the abuse of the newly formulated concept, which has to be curbed.
Keywords: Business failure; Companies Act 71 of 2008; South Africa

A critical analysis of the role, appointment, and powers of a business rescue practitioner - Luthuli, Bayanda Nompumelelo (University of KwaZulu-Natal, 2022)
No abstract provided.
Keywords: Corporate rescue regime; Financially distressed companies; Judicial management

The abuse of dominant position in digital markets: Google Shopping case - Moroni, Filippo (LUISS Guido Carli, 2022)
Abuse of dominance in the digital markets. Digital markets. Art.102 TFEU: how can it be applied to digital markets? A global perspective: the evolution of the abuse of dominance in digital markets around the world. Europe: the proposal for a regulation on contestable and fair markets in the digital sector (digital market act). United States of America: a time for reforms. China: a new approach towards digital markets. The Google Shopping case: the first step for competition enforcement in digital markets. The European Commission decision (AT.39740). The general Court decision (T-612/17). The Google case in the US: completely different results. A glimpse into the future: the Google Shopping case under the DMA.
Keywords: Abus de position dominante; Competencia; Competition law; Concurrence; Dominant position; Monopole

The use of blockchain technology in international commercial transactions, with specific reference to secured payments in international contracts of sale - Muza, Chido Teclar Mitchel (University of Johannesburg, 2022)
Please refer to full text to view abstract.
Keywords: Blockchains (Databases); Commercial law; Electronic funds transfers; Export sales contracts.; Foreign trade regulation

Conflict Management over Maritime Territories : Use of ADR in Maritime Disputes: Kenya vs Somalia - Mwala, Natasha Lulia (Universität Wien, 2022)
The recent discoveries of natural resources on both territorial and maritime borders have heightened the probability of conflicts between states specifically in the Horn of Africa and the Greater Lakes Region. As a highly volatile region, conflicts are not a foreign phenomenon which have been plaguing the region since transition to the post-colonial era. It is simple to argue that the cause of disputes is due to the arbitrary borders drawn by the European powers, however, the region is experiencing a contemporary ‘scramble and petition’ with countries racing to exploit and gain over the newfound resources. In addition to this, the rise of nationalist sentiments combined with the burgeoning population and struggle of governments to finance their domestic budgets while trying to reduce borrowing from foreign markets due to the inflation costs which makes it expensive, also plays a key role in the quest to benefit from mineral exploration and excavation. While traditional conflicts rose from land border disputes that escalated to violence especially between border communities, maritime conflicts tend to be handled in legal ways with parties seeking intervention from bodies such as the International Tribunal of the Law of the Sea (ITLOS) and the International Court of Justice (ICJ). Most cases are solved by outright delimitation of the maritime borders rather that joint management of marine land masses or natural resources based on mutual understanding or mutually assured benefits. The recent Kenya-Somalia Maritime dispute is an excellent case study. The aim of this research is to not only show alternative dispute resolution methods that can be used in maritime border disputes but also analyse the switch from pacific means of settlement of disputes to judicial intervention of the court. It begins by looking at the evolution of land border disputes between the two states, touches on the maritime dispute and their diplomatic, economic and security relationship. It further critically analyses the points of view of the two countries and the court’s ruling. Finally, it examines alternative dispute settlement mechanism that could have been used.
Keywords: ICJ; Joint maritime agreement; LOS; Maritime boundary dispute; Maritime délimitation; Memorandum of understanding

The Processes of Democratization and Economic Development in Africa: A Case Study of the Democratic Republic of Congo (DRC) Since 2006 - Otshudi Talo, Esperance (Near East University, 2022)

A legal comparison on the effectiveness of judicial management in Botswana against business rescue in South Africa - Topi, Sharon (University of Johannesburg, 2022)
Please refer to full text to view abstract.